Two new subfamilies, three new species and a new subspecies of dendrochirotid sea cucumbers (Echinodermata: Holothuroidea) - Thandar, Ahmed S. (Zootaxa, 2017)
Some materials in the Natural History Museum, London, originating from various parts of the world, proved on examination, to comprise two new species herein described as Cladodactyla pesdispersa n. sp. and Thyonina rasidae n. sp., and a new subspecies, Havelockia ferali andamanensis n. subsp. In addition, some specimens examined from the museum collections of the Department of Aquatic Biology and Fisheries, University of Kerala in India contained, besides the well-known dendrochirotids, Aslia forbesi (Bell) and Stolus buccalis (Stimpson), two specimens which proved to also represent a new species of Thyonina, herein described as Thyonina bijui n. sp., as it differs significantly from T. rasidae n. sp. from Pakistan and the South African T. articulata Vaney. For the genus Thyonina, currently attributed to the subfamily Thyoninae, a new subfamily Thyonininae is here diagnosed. In addition a new subfamily Hemithyoninae is proposed for Hemithyone semperi (Bell), also placed in the Thyoninae till now.